Odpowiedzi

2010-03-22T17:49:04+01:00
A)x+36,95=60
x=60-36,95
x=23,05
b)23,5+x=356,3
x=356,3-23,5
x=332,8
c)49,62-x=23,485
x=49,62-23,485
x=26,135
d)x-5,28=2,305
x=2,305+5,28
x=7,585
e)75,2-x=36,64
x=75,2-36,64
x=38,56
f)19,6+x=20,01
x=20,01-19,6
x=0,41
g)401,05-x=285,883
x=401,05-285,883
x=115,167
h)76,1-x=25,04
x= 76,1-25,04
x=51,06
3 3 3
2010-03-22T17:50:32+01:00
A)x+36,95=60
x = 60 - 36,95
x = 23.05
b)23,5+x=356,3
x= 356,3 - 23,5
x=332,8
c)49,62-x=23,485
-x= 23,485 - 49, 62
-x=-26,135 / (-1)
x = 26,135
d)x-5,28=2,305
x = 2,305 + 5,28
x=7,585
e)75,2-x=36,64
-x = 36,64 - 75,2
-x = - 38,56 /(-1)
x= 38,56
f)19,6+x=20,01
x = 20,01 - 19,6
x = 0,41
g)401,05-x=285,883
- x = 285,883 - 401,05
- x = - 115,167 /(-1)
x = 115,167
h)76,1-x=25,04
- x = 25,04- 76,1
- x = - 51,06 /(-1)
x = 51,06